Phenotypic and Genotypic Antimicrobial Susceptibility Testing of Chlamydia trachomatis Isolates from Patients with Persistent or Clinical Treatment Failure in Spain - Laura Villa; José Antonio Boga; Luis Otero; Fernando Vazquez; Ana Milagro; Paula Salmerón; Martí Vall-Mayans; María Dolores Maciá; Samuel Bernal; Luis Piñeiro (MDPI AG, 2023)
The aim of this multicentre project (seven hospitals across the Spanish National Health Service) was to study the phenotypic and genotypic susceptibility of C. trachomatis to the main antimicrobials used (macrolides, doxycycline, and quinolones) in isolates from patients with clinical treatment failure in whom reinfection had been ruled out. During 2018-2019, 73 clinical isolates were selected. Sixty-nine clinical specimens were inoculated onto confluent McCoy cell monolayers for phenotypic susceptibility testing. The minimum inhibitory concentration for azithromycin and doxycycline was defined as the lowest concentration associated with an at least 95% reduction in inclusion-forming units after one passage in the presence of the antibiotic compared to the initial inoculum for each strain (control). Sequencing analysis was performed for the genotypic detection of resistance to macrolides, analysing mutations in the 23S rRNA gene (at positions 2057, 2058, 2059, and 2611), and quinolones, analysing a fragment of the gyrA gene, and searching for the G248T mutation (Ser83->Ile). For tetracyclines, in-house RT-PCR was used to test for the tet(C) gene. The phenotypic susceptibility testing was successful for 10 isolates. All the isolates had minimum inhibitory concentrations for azithromycin ≤ 0.125 mg/L and for doxycycline ≤ 0.064 mg/L and were considered sensitive. Of the 73 strains studied, no mutations were found at positions T2611C or G248T of the gyrA gene. We successfully sequenced 66 isolates. No macrolide resistance-associated mutations were found at positions 2057, 2058, 2059, or T2611C. None of the isolates carried the tet(C) gene. We found no evidence for genomic resistance in this large, clinically relevant dataset.